Occupational therapy for physical dysfunction - Trombly, Catherine Anne, ....-; Radomski, Mary Vining, ....- (Philadelphia : Lippincott, Williams and Wilkins, 2002)
1. Occupatioanl function: definition, process and history 2. Assessment of occupational function 3. Therapeutic mechanisms 4. Therapeutic technologies 5. treatment of occupational function 6. Treatment to promote occupational function for selected diagnostic categories
Keywords: Ergotherapie